The end of the Chinese dream : why Chinese people fear the future - Lemos, Gerard (Yale University Press, 2012)
"Glossy television images of happy, industrious, and increasingly prosperous workers show a bright view of life in twenty-first-century China. But behind the officially approved story is a different reality. Preparing this book Gerard Lemos asked hundreds of Chinese men and women living in Chongqing, an industrial mega-city, about their wishes and fears. The lives they describe expose the myth of China's harmonious society. Hundreds of millions of everyday people in China are beleaguered by immense social and health problems as well as personal, family, and financial anxieties--while they watch their communities and traditions being destroyed. Lemos investigates a China beyond the foreigners' beaten track. This is a revealing account of the thoughts and feelings of Chinese people regarding all facets of their lives, from education to health care, unemployment to old age, politics to wealth. Taken together, the stories of these men and women bring to light a broken society, one whose people are frustrated, angry, sad, and often fearful about the circumstances of their lives. The author considers the implications of these findings and analyzes how China's community and social problems threaten the ambitious nation's hopes for a prosperous and cohesive future. Lemos explains why protests will continue and a divided and self-serving leadership will not make people's dreams come true"--